Intracellular microRNA expression patterns influence cell death fates for both necrosis and apoptosis. Issue 11 (22nd October 2020) - Sato, Akira; Yamamoto, Akihiro; Shimotsuma, Akira; Ogino, Yoko; Funayama, Naoki; Takahashi, Yui; Hiramoto, Akiko; Wataya, Yusuke; Kim, Hye‐Sook
Abstract : MicroRNAs (miRNAs) are small noncoding RNA molecules that interact with target mRNAs at specific sites to induce cleavage of the mRNA or inhibit translation. Such miRNAs play a vital role in gene expression and in several other biological processes, including cell death. We have studied the mechanisms regulating cell death (necrosis in original F28‐7 cells and apoptosis in their variant F28‐7‐A cells) in the mouse mammary tumor cell line FM3A using the anticancer agent floxuridine (FUdR). We previously reported that inhibition of heat‐shock protein 90 by the specific inhibitor geldanamycin (GA) in F28‐7 cells causes a shift from necrosis to apoptosis. In this study, we investigated the intracellular miRNA expression profiles of FUdR‐treated F28‐7 cells (necrotic condition), GA plus FUdR‐treated F28‐7 cells (apoptotic condition), and FUdR‐treated F28‐7‐A cells (apoptotic condition) through miRNA microarray analysis. In addition, we knocked down Dicer, a key molecule for the expression of mature miRNAs, in F28‐7 cells to examine whether it modulates FUdR‐induced cell death. Our analysis revealed that the miRNA expression patterns differ significantly between these cell death conditions. Furthermore, we identified miRNA candidates that regulate cell death. Knockdown of Dicer in FUdR‐treated necrosis‐fated cells caused a partial shift from necrosis to apoptosis. These findings suggest that modulation of miRNA expression patterns influences the decision of cell death fate toward necrosis or apoptosis. Our findings may serve as a basis for further study of the functions of miRNAs in cell death mechanisms. Abstract : We reveal that intracellular miRNA expression patterns are dramatically altered in necrosis and apoptosis using a floxuridine (FUdR)‐induced mouse mammary tumor cell death model. We found that knockdown of Dicer in FUdR‐treated necrosis‐fated cells caused a partial shift from necrosis to apoptosis. These findings suggest that the expression of miRNA(s) regulates cell death fate toward necrosis or apoptosis.